2010
DOI: 10.1107/s1600536810021100
|View full text |Cite
|
Sign up to set email alerts
|

(4-Chlorophenyl)methanaminium chloride hemihydrate

Abstract: In the title hydrated salt, C7H9ClN+·Cl−·0.5H2O, the water O atom lies on a crystallographic twofold axis. In the crystal, the monoprotonated 4-chloro­benzyl­ammonium cation forms N—H⋯Cl and N—H⋯O hydrogen bonds and the water mol­ecule forms O—H⋯Cl hydrogen bonds, generating layers lying parallel to the bc plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…3 and Table 1). Souissi et al (2010) have reported the related crystal structure of (4-chlorophenyl)methanaminium chloride hemihydrate.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…3 and Table 1). Souissi et al (2010) have reported the related crystal structure of (4-chlorophenyl)methanaminium chloride hemihydrate.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…Furthermore, the crystal structure is stabilized by C1-H1BÁ Á Á iii and C8-H8AÁ Á Á i weak interactions involving the C2-C7 benzene ring, to form a threedimensional network (see Table 1). Souissi et al (2010) have reported the crystal structure of (4-chlorophenyl)-methanaminium chloride hemihydrate, in which the water O atom lies on a crystallographic twofold axis.…”
Section: Structure Descriptionmentioning
confidence: 99%